Early category and concept development : making sense of the blooming, buzzing confusion - Rakison, David H., 1969-; Oakes, Lisa M., 1963- (Oxford University Press, 2003)
This text brings together contemporary findings and theories about the origins and early development of categorization and conceptual abilities. Despite advances in our understanding of this area, a number of hotly debated issues remain at the centre of the controversy over categorization.
Keywords: Cognition in infants.; Perception in infants.; Cognition.; Child development.; Perception.; Children.; Infants.; Cognition; Child Development; Concept Formation; Perception; Child; Infant; Cognition chez le nourrisson.; Perception chez le nourrisson.; Enfants -- Développement.; Enfants.; Nourrissons.; cognition.; children (people by age group); infants.; FAMILY & RELATIONSHIPS -- Life Stages -- Infants & Toddlers.; Infants; Children; Child development; Cognition in infants; Perception in infants; Samfundsvidenskab -- Psykologi.